Form, function, and phylogeny of bivalve mucins - Prezant, Robert (1990)
Keywords: dept.aa

Shell and hinge ontogeny of the Antarctic bivalve Lissarca notorcadensis - Prezant, Robert (Journal of the Marine Biological Association of the United Kingdom, 1990)
Lissarca notorcadensis, a small pallial-brooding mollusc with a circum-Antarctic distribution, is frequently found attached by stout byssal threads to the spines of sea urchins. Here, complete ontogenetic series can be found. Using standard, structural definitions, the prodissoconch I of L. notorcadensis is small compared to the large prodissoconch II, a feature atypical of brooded young and possibly reflective of a planktotrophic past. Fine commarginal striae are found on prodissoconch II of this subtidal clam, which also possesses more pronounced commarginal striae on the dissoconch prior to brood release. The provinculum is retained and remains functional well into adulthood. A small central ligament pit is present through the postlarval stages. This develops into a large, triangular pit in adulthood that shows obvious growth lines. Calcareous, presumably aragonitic fibres develop in the ligament of specimens still retained in the adult brood. Five to six adult hinge teeth are formed on either side of the ligament. Alignment of shell valves by these well-developed teeth is augmented by retention of larval denticles. The functional and structural demise of the provinculum occurs between 4 and 7 mm shell height and results from denticle erosion and subumbonal shell overgrowth. Many canals permeate larval and adult valves, but external pores in the adult shell differ from those of the larval shell and could indicate mode of formation. Prodissoconch form, provinculum retention, and shell canals are considered primitive traits.
Keywords: dept.aa